2020
DOI: 10.3390/cancers12113216
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Proton and Photon Irradiation Combined with Pharmacological Inhibitors in 3D Pancreatic Cancer Cultures

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly therapy-resistant tumor entity of unmet needs. Over the last decades, radiotherapy has been considered as an additional treatment modality to surgery and chemotherapy. Owing to radiosensitive abdominal organs, high-precision proton beam radiotherapy has been regarded as superior to photon radiotherapy. To further elucidate the potential of combination therapies, we employed a more physiological 3D, matrix-based cell culture model to assess tumoroid formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Firstly, we observed equal efficacy of protons and photons regarding the clonogenic survival and DSB induction and repair, which is in line with the notion of similar radiobiological effectiveness between photons and protons [ 7 , 24 ]. Such similarities of photon and proton irradiation have also been found for pancreatic ductal adenocarcinoma [ 21 ], glioma stem cells [ 25 ] and lung cancer [ 26 ]. As a sufficient repair of DNA damage reflects one major determinant of intrinsic cellular radiosensitivity, the similarity in DSB repair in photon- and proton-irradiated cells further underscores our clonogenic survival data.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Firstly, we observed equal efficacy of protons and photons regarding the clonogenic survival and DSB induction and repair, which is in line with the notion of similar radiobiological effectiveness between photons and protons [ 7 , 24 ]. Such similarities of photon and proton irradiation have also been found for pancreatic ductal adenocarcinoma [ 21 ], glioma stem cells [ 25 ] and lung cancer [ 26 ]. As a sufficient repair of DNA damage reflects one major determinant of intrinsic cellular radiosensitivity, the similarity in DSB repair in photon- and proton-irradiated cells further underscores our clonogenic survival data.…”
Section: Discussionmentioning
confidence: 72%
“…As alternative approach and based on our knowledge of the radiosensitizing potential of DNA repair inhibitors [ 15 , 21 , 22 ], we tested whether such inhibitors result in comparable radiosensitization of 3D HNSCC cell cultures exposed to photon or proton irradiation. Our observations in the ATM-deficient HNSCC cell line SKX, which showed higher radiosensitivity to protons relative to photons, prompted us to evaluate the efficacy of pharmacological inhibitors targeting a number of key enzymes of the two major DSB repair pathways non-homologous end joining (NHEJ) and homologous recombination (HR) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Görte et al evaluated phosphoproteomics changes after photon and proton irradiation and showed that proton therapy stimulates greater phosphoproteome changes compared to photon. Moreover, targeting classical and alternative NHEJ enhanced therapeutic ratio either with photon or proton [ 24 ].…”
Section: Discussionmentioning
confidence: 99%